THE INTERRELATIONSHIP BETWEEN CARDIOMETABOLIC MULTIMORBIDITY AND LATE-LIFE DEPRESSION: FROM PATHOPHYSIOLOGY TO CLINICAL IMPLICATIONS – A NARRATIVE REVIEW - Katarzyna Andrzejewska,; Wiktor Golus,; Paweł Edyko,; Alicja Babula,; Zuzanna Przybyła,; Bartosz Golis,; Anna Maria Gęsińska,; Hubert Woźniak,; Krystian Czyżkowski,; Helena Szelka, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and objective: Late-life depression (LLD) is a complex mood disorder that rarely occurs in isolation, frequently co-existing with cardiometabolic multimorbidity (CMM). This comorbidity triggers a cascade of adverse consequences, including accelerated biological aging and increased mortality. The objective of this narrative review is to synthesize current knowledge on the bidirectional relationship between CMM and LLD, exploring pathophysiological mechanisms from the Vascular Depression (VaDep) hypothesis to clinical implications.Description of the state of knowledge: Epidemiological evidence indicates a strong "dose-response" relationship, where cumulative cardiometabolic burden amplifies the risk of incident depression. The review discusses the neuroimaging correlates of VaDep, particularly white matter hyperintensities, while addressing the "neuropathological paradox" observed in postmortem studies. Key pathogenic pathways identified include chronic low-grade inflammation ("inflamm-aging"), endothelial dysfunction, and the "metabolic-brain axis," specifically in type 2 diabetes. Furthermore, the analysis highlights the role of shared genetic susceptibility and the phenomenon of "joint trajectories," where physical, cognitive, and mood decline occur synchronously.Conclusions: LLD in the context of CMM constitutes a distinct clinical phenotype driven by systemic vascular and metabolic dysregulation. Current evidence necessitates a paradigm shift from isolated psychiatric management to an integrated, interdisciplinary approach. Aggressive control of vascular risk factors, potential anti-inflammatory strategies, and social prescribing are pivotal for breaking the vicious cycle of multimorbidity and improving long-term prognosis.